ACCOUNTING IN THE LIBERAL ARTS COLLEGE. - Murphy, Mary E. (The Accounting Review, 1952)
Abstract The approach to courses for all fields of accounting, public, private, cost, tax and governmental, represents something of a paradox today. Viewed by some as too practical for admission to the cultural-centered liberal arts curriculum, by others as a field of graduate study, these courses on many campuses have been sustained largely by the intellectual prowess of faculties and the ever-increasing demand of students for practical training in areas of employment arising from the war and post-war economics. Even the most cursory glance at recent college catalogues reveals that accounting courses appear under a variety of departments, most frequently under business administration or social science, but sometimes correlated with instruction in mathematics, statistics or secretarial studies, and less frequently as part of the pre-engineering or pre-law curriculum. Teachers of all phases of accountancy in liberal arts colleges, and indeed in other institutions of higher learning, have made a valiant, if at times a somewhat ineffectual, effort to train students to cope with the rapidly shifting economic climate, and to relate the complex technical knowledge of this age to human progress.